2015
DOI: 10.1111/lasr.12150
|View full text |Cite
|
Sign up to set email alerts
|

Trailblazers and Those That Followed: Personal Experiences, Gender, and Judicial Empathy

Abstract: This article investigates one causal mechanism that may explain why female judges on the federal appellate courts are more likely than men to side with plaintiffs in sex discrimination cases. To test whether personal experiences with inequality are related to empathetic responses to the claims of female plaintiffs, we focus on the first wave of female judges, who attended law school during a time of severe gender inequality. We find that female judges are more likely than their male colleagues to support plain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…While overt discrimination has undoubtedly lessened compared to earlier eras (Moyer and Haire, ), the evidence indicates that bias against outsider groups has continued to prevail, to a lesser extent, in the legal profession and in the courtroom . However, the extensive body of work cataloging discriminatory treatment faced by women and minorities in the legal profession has generally viewed these as discrete and not overlapping phenomena .…”
Section: Bias and Stereotyping In The Legal Professionmentioning
confidence: 92%
“…While overt discrimination has undoubtedly lessened compared to earlier eras (Moyer and Haire, ), the evidence indicates that bias against outsider groups has continued to prevail, to a lesser extent, in the legal profession and in the courtroom . However, the extensive body of work cataloging discriminatory treatment faced by women and minorities in the legal profession has generally viewed these as discrete and not overlapping phenomena .…”
Section: Bias and Stereotyping In The Legal Professionmentioning
confidence: 92%
“…Emotional intelligence, time management, compassion, and negotiation are all skills built through the many roles women serve in our society (O'Leary, Choi, and Gerard 2012). These attributes position women to have a unique understanding of the complex social problems that public administrators work to solve, both in the academy and in practice (Moyer and Haire 2015). These “soft skills” are becoming increasingly important as collaborative work in governance expands its influence (O'Leary, Choi, and Gerard 2012).…”
Section: The Missing Linksmentioning
confidence: 99%
“…Situational empathy occurs when individuals' own direct experiences with an issue result in their being more sensitive when the same problem is experienced by others, and subsequently are willing to champion the other people's situations (Plumm and Terrance ). For example, Moyer and Haire () found that women judges who report having experienced sexual discrimination themselves were more likely to have empathy with women plaintiffs claiming discrimination. Specifically, they found that “judicial empathy for a plaintiff who alleges discriminatory treatment is not borne from a trait [such as both judge and plaintiff being female], but instead appears to form from [similar] experiences with discrimination” (Moyer and Haire : 684).…”
Section: Empathy and Out‐group Alliesmentioning
confidence: 99%
“…This is similar to the judges in Moyer and Haire's study of empathy with women plaintiffs in sex discrimination cases. If the women judges had experienced discrimination themselves, their empathy for these plaintiffs was greater ().…”
Section: Pumping Rights and Managerial Lactivismmentioning
confidence: 99%